HLA variations in patients with diffuse large B-cell lymphoma and association with disease risk and prognosis: a case-control study - Diamanti, Ioanna; Fylaktou, Asimina; Verrou, Evgenia; Vlachaki, Efthimia; Sinakos, Manolis; Katodritou, Eirini; Ouranos, Konstantinos; Minti, Fani; Gioula, Georgia (Frontiers in Genetics, 2024)
Human leukocyte antigen (HLA) polymorphisms have been associated with the development of malignant neoplasms. Non-Hodgkin lymphomas (NHLs) are a heterogenous group of lymphoid malignancies in which a genetic substrate has been established. This study aimed to identify whether variations in the HLA gene region were associated with diffuse large B-cell lymphoma (DLBCL) risk and prognosis. We defined HLA class I (HLA-A, HLA-B, HLA-C) and class II (HLA-DRB1, HLA-DQB1) alleles in 60 patients with DLBCL and compared the results to those found by 236 healthy adult donors from the bone marrow bank of Northern Greece. HLA typing was performed by two molecular methods, Sequence -Specific Oligonucleotide HLA typing (SSO) and Sequence -Specific Primer HLA typing (SSP), from white blood cells recovered from peripheral blood. The phenotypic frequencies of HLA-A, HLA-B, HLA-C, HLA-DRB1 and HLA-DQB1 between patients and controls were compared with the 2-sided Fisher's exact test. Results with p-value < 0.05 were considered statistically significant. Odds Ratios with 95% Confidence Intervals were calculated to further strengthen the results. The 2-sided Fisher's exact test was also applied to alleles found only in one of the two groups, while the odds ratios together with the confidence intervals were corrected with Haldane-Anscombe method. Among the studied HLA polymorphisms, the frequency HLA-C*12 allele was significantly lower in patients with DLBCL compared with control subjects (6.7% vs 34.7%, OR=0.16, 95% CI: 0.04-0.44). Frequency of HLA-B*39 was significantly lower in patients with DLBCL compared with controls, but due to the low frequency of this polymorphism in the studied population and small sample size, determinations regarding the significance of this findings were limited. Survival analysis revealed that the presence of HLA-C*12 was not associated with improved or worsened overall and progression-free survival. No statistically significant associations were observed in the phenotypic frequencies of HLA-A, HLA-DQB1, HLA-DRB1 and the rest of HLA-B alleles between the control and DLBCL groups. Collectively, our results provide valuable insight regarding the role of HLA variations on DLBCL risk. Further studies are required to consolidate our findings and ascertain the clinical implications of these genetic variations on DLBCL management and prognosis.